Private antitrust enforcement: facilitating injured parties’ access to legal remedies in competition law cases, 2022 - Danov, Mihail (UK Data Service, 2024)
A specific feature of many competition law infringements is that they would cause harm to multiple injured parties (e.g. large businesses, small and medium-size enterprises, consumers). This means that related claims which raise common issues of law / fact and which arise out of the same infringement are bound to arise. The complex issues concerning the case-management of multiple and related claims were exposed in Interchange Fee litigation as well as in the Trucks litigation. It is hypothesised that existing procedural deficiencies inflate litigation costs, which in turn adversely affect private parties’ access to justice in competition law cases. New empirical data was brought together to test the relevant hypotheses. On the basis of the newly collected data, it is possible to identify the challenges in relation to quantification of damages and case management of multiple related claims arising out of the same infringement. The research methodology is developed around litigants’ strategies. An analysis of the litigants’ strategies is important to ascertain how the private antitrust litigation regime is functioning in England and Wales. The relevant data was collected through: 1) Self-completion surveys: Law firms and litigation funders were surveyed with a view to collecting quantitative data concerning the number and value of the claims, litigation costs and relevant outcomes (e.g. judgments / settlements). Whereas data from law firms could help the factors which promote and / or hinder settlements. Data from litigation funders could also be indicative about the relevant proportion of funded / non-funded claims as well as about the major aspects which impact on the funders’ decision to fund private antitrust damages. 2) Semi-structured interviews were conducted with legal practitioners. The collected qualitative data the aspects of the enforcement regime (e.g. disclosure rules, case-management mechanisms) along with the relevant attributes of the claims (e.g. value of the claim and exposure to damages; prospects of success; related proceedings) which impact on the litigants’ strategies and which affect the litigants strategies and any settlement dynamics (influencing the case outcome). An analysis of collected data should demonstrate how the uncertainty about the outcome would affect the litigants’ strategies that would impact on the settlement dynamics, undermining the effectiveness and efficiency of the current private antitrust litigation regime. On that basis, it should be possible to consider practical solutions which are aiming to address (or at least reduce) the identified deficiencies with a view to improving the injured parties’ timely access to effective legal remedies. The project advances an argument that devising a mechanism, which enables judges to deal with numerous related claims arising out of the same competition law infringement, is central to improving access to legal remedies for multiple injured parties (consumers, small and large businesses) bringing private antitrust damages claims in England. The project paper draws on an empirical study which was carried out in 2022. New quantitative and qualitative data was collected from law firms, litigation funders and legal practitioners. The newly collected data demonstrates how the current private antitrust enforcement regime is functioning. The collected data goes further to capture the factors affecting settlements which remain the most desirable and common outcome in competition law claims. The data analysis enables the author to identify the major legal aspects along with the main attributes of the claims which shape litigants’ strategies. Since the high litigation costs - which are fuelled by the existing uncertainty about the outcome - are major considerations, it is suggested that devising an effective and efficient case-management mechanism may be necessary for judges to be able to award appropriate legal remedies within reasonable time and at proportionate cost. Such a mechanism should foster settlements and further incentivise litigation funders to finance competition law claims. The relevant journal article is to be published in the Global Competition Litigation Review - issue 3/2024.